β -Irida-graphene: A new 2D carbon allotrope for sodium-ion battery anodes - Laranjeira, José A.S. [UNESP]; Lima, Kleuton A.L.; Martins, Nicolas F. [UNESP]; Ribeiro, Luiz A.; Galvão, Douglas S.; Cabral, Luis A. [UNESP]; Sambrano, Julio R. [UNESP] (Elsevier, 2025)
The quest for sustainable and efficient energy storage has driven the exploration of sodium-ion batteries (SIBs) as promising alternatives to lithium-ion systems. However, the larger ionic radius of sodium poses intrinsic challenges such as slow diffusion and structural strain in conventional electrode materials. As a contribution to addressing these limitations, the β -Irida-graphene ( β -IG) is herein introduced, a novel two-dimensional (2D) carbon allotrope derived from Irida-graphene, featuring a diverse polygonal lattice of 3-, 4-, 6-, 8-, and 9-membered carbon rings. Through density functional theory and ab initio molecular dynamics simulations, β -IG demonstrated remarkable thermal, dynamical, and mechanical stability, coupled with intrinsic conductive character and efficient sodium-ion mobility (energy barriers ¡ 0.30 eV). Furthermore, the adsorption of sodium ions was energetically favorable, delivering an impressive predicted specific capacity of 554.5 mAh/g. The reported findings highlight β -IG as a good potential anode candidate for next-generation SIBs, offering high-rate performance and structural robustness, and expanding the functional design space for advanced carbon-based electrode materials.